1999
DOI: 10.1016/s0002-9270(99)00360-3
|View full text |Cite
|
Sign up to set email alerts
|

Is virtual colonoscopy a cost-effective option to screen for colorectal cancer?

Abstract: To become cost-effective and be able to compete with colonoscopy in screening for colorectal cancer, CT or MR colonography would need be offered at a very low price or result in compliance rates much better than those associated with colonoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 0 publications
1
50
0
1
Order By: Relevance
“…localized, regional, and distant) with those of colonoscopy, all the available simulation models available in the literature (see Table 1) consistently indicate the efficacy of CTC in reducing both CRC incidence and mortality, ranging from 40% to 77% for reduction in CRC incidence (prevention) and from 58% to 84% for CRC mortality reduction. 1522 Several factors may explain this inter-study variability: The rate of de novo CRC versus benign polyp precursorThe type and prevalence of polyp size classesThe simulated stages of CRCThe rate of progression through the different types of polyps and CRC stagesInput assumptions of CTC accuracyThe impact of extra-colonic findings.…”
Section: Can Ctc Reduce Crc Incidence and Mortality?mentioning
confidence: 99%
See 1 more Smart Citation
“…localized, regional, and distant) with those of colonoscopy, all the available simulation models available in the literature (see Table 1) consistently indicate the efficacy of CTC in reducing both CRC incidence and mortality, ranging from 40% to 77% for reduction in CRC incidence (prevention) and from 58% to 84% for CRC mortality reduction. 1522 Several factors may explain this inter-study variability: The rate of de novo CRC versus benign polyp precursorThe type and prevalence of polyp size classesThe simulated stages of CRCThe rate of progression through the different types of polyps and CRC stagesInput assumptions of CTC accuracyThe impact of extra-colonic findings.…”
Section: Can Ctc Reduce Crc Incidence and Mortality?mentioning
confidence: 99%
“…The available models indicate that CTC is effective in reducing both CRC incidence and mortality, ranging from 40% to 77% for CRC incidence prevention and from 58% to 84% for CRC mortality reduction. 1522 Several factors may explain this inter-study variability, such as the assumed rate of de novo CRC, the type and prevalence of polyp size classes, the simulated stages of CRC, the progression through the different types of polyps and CRC stages, CTC accuracy, and extra-colonic findings. CTC has been consistently shown to be cost-effective as compared with no screening, indicating that it represents at the very least an attractive test for individuals who are non-compliant with the available options.…”
mentioning
confidence: 99%
“…Colonoscopy allows inspecting the whole colon and removing detected polyps. However, “the method is time consuming, rather expensive, requires bowel preparation, it is unpleasant for the patients” [30]. Virtual colonoscopy avoids painful bowel preparation performed in conventional colonoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Early cost-effectiveness analyses from the US concluded that a screening strategy employing CT colonography is more costly than one using colonoscopy every 10 years 70 71. These analyses used outdated CTC performance characteristics or a fixed screening interval of 10 years.…”
Section: Cost-effectivenessmentioning
confidence: 99%